Mastite clínica em fêmea da raça girolando - Gabriela Santos Moura, Adha (Universidade Federal do Tocantins, 2022)
The activities that made up the mandatory supervised curricular internship in Veterinary Medicine were developed at JA Saúde Animal, in the city of Araguaína-TO, in the areas of Clinical Medicine and Veterinary Surgery, from May 11 to July 9, 2021, making up a total of 345 hours, under the supervision of the Veterinary Doctor Guaraci Lima Reis and the guidance of Prof. Dr. Katyane de Sousa Almeida. The internship began with activities inherent to the commercial routine and technical visits to the properties in the region, where protocols were carried out to intervene in any diseases that affected the animals. During the internship, clinical and surgical cases were attended to, materials were collected for exams, veterinary appointment and sanitary protocols inserted, and participation in training sessions. This report presents the description of the internship site and routine monitoring of the veterinarian, having as its main theme the clinical case report of Clinical Mastitis in a female bovine, attended, evaluated and treated, responding well to treatment and presenting clinical cure.